2023
DOI: 10.1186/s12933-023-01816-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights into SGLT2 inhibitor treatment of diabetic cardiomyopathy: focus on the mechanisms

Abstract: Among the complications of diabetes, cardiovascular events and cardiac insufficiency are considered two of the most important causes of death. Experimental and clinical evidence supports the effectiveness of SGLT2i for improving cardiac dysfunction. SGLT2i treatment benefits metabolism, microcirculation, mitochondrial function, fibrosis, oxidative stress, endoplasmic reticulum stress, programmed cell death, autophagy, and the intestinal flora, which are involved in diabetic cardiomyopathy. This review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 222 publications
0
11
0
Order By: Relevance
“…The different SGLT2i subtypes also differ in terms of efficacy and indication. 41 Clinical studies have shown that empagliflozin and dapagliflozin are inconsistent, especially in terms of cardiovascular death. 42 The inconsistency in cardiovascular death between empagliflozin and dapagliflozin may be due to the intrinsic pharmacological difference.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The different SGLT2i subtypes also differ in terms of efficacy and indication. 41 Clinical studies have shown that empagliflozin and dapagliflozin are inconsistent, especially in terms of cardiovascular death. 42 The inconsistency in cardiovascular death between empagliflozin and dapagliflozin may be due to the intrinsic pharmacological difference.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In recent years, sodium‐glucose cotransporter‐2 (SGLT‐2) inhibitors have demonstrated significant promise in the treatment of DCM. 39 , 40 , 41 , 42 , 43 , 44 , 45 Commonly used SGLT‐2 inhibitors include empagliflozin, dapagliflozin, and canagliflozin. 39 As opposed to conventional insulin‐dependent hypoglycemic medications, SGLT‐2 inhibitors work to lower blood glucose by inhibiting SGLT‐2R on the renal tubules, reducing glucose reabsorption from the tubules and increasing excretion, and to some extent inhibiting SGLT‐1R on the intestine, reducing glucose absorption and utilization in the small intestine to achieve hypoglycemic effects.…”
Section: Recent Advances In Treatment Researchmentioning
confidence: 99%
“… 39 , 40 , 41 , 42 , 43 , 44 , 45 Commonly used SGLT‐2 inhibitors include empagliflozin, dapagliflozin, and canagliflozin. 39 As opposed to conventional insulin‐dependent hypoglycemic medications, SGLT‐2 inhibitors work to lower blood glucose by inhibiting SGLT‐2R on the renal tubules, reducing glucose reabsorption from the tubules and increasing excretion, and to some extent inhibiting SGLT‐1R on the intestine, reducing glucose absorption and utilization in the small intestine to achieve hypoglycemic effects. 39 SGLT‐2 inhibitors enable higher urine glucose and sodium excretion, and decreased blood volume in a chronic hyperglycemic setting, lowering cardiac Preload and afterload and raising cardiac output.…”
Section: Recent Advances In Treatment Researchmentioning
confidence: 99%
“…Despite the remarkable consistency of the benefit of the SGLT‐2is on a range of outcomes in patients with HF, type 2 diabetes and CKD, there is still uncertainty as to how these drugs work in each setting. 20 , 21 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Despite being developed as glucose‐lowering medications, they are effective in patients without type 2 diabetes with HF and kidney disease. It may be that different postulated mechanisms are more or less important in each disease.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%